2016
DOI: 10.1080/13527258.2016.1218912
|View full text |Cite
|
Sign up to set email alerts
|

Effective or not? Success or failure? Assessing heritage and archaeological education programmes – the case of Çatalhöyük

Abstract: Recent decades have witnessed an increasing involvement of archaeology projects in planning and carrying out heritage education programmes to increase heritage awareness among the public. This paper aims to explore ways in which models of education programmes in public archaeology could be more effective in ensuring the protection of heritage sites by examining the one of the worlds longest-running education programme, run by the Çatalhöyük Research Project in Turkey. It is important to pay attention to multi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 29 publications
0
13
0
2
Order By: Relevance
“…One of the significant contributions of the programme was to consider the social, cultural and economic backgrounds of the participants and running the programme accordingly. This significant aspect of informal education is very often neglected in devising education programmes (Apaydin 2016b). The education board of the city and local NGOs assisted in the selection process of children for the education programme.…”
Section: Public Engagement and Educationmentioning
confidence: 99%
“…One of the significant contributions of the programme was to consider the social, cultural and economic backgrounds of the participants and running the programme accordingly. This significant aspect of informal education is very often neglected in devising education programmes (Apaydin 2016b). The education board of the city and local NGOs assisted in the selection process of children for the education programme.…”
Section: Public Engagement and Educationmentioning
confidence: 99%
“…Community engagement projects include meetings and festivals held in collaboration with the locals who live in close proximity to the site (see Atalay 2012). However, a recent study that focused on the evaluation of these programs revealed that public engagement and heritage education is still necessary, preferably from a bottom-up perspective (see Apaydin 2015Apaydin , 2016b. The inhabitants of Konya and villages near Çatalhöyük understand the past along specifically religious dimensions, emphasizing Ottoman history and the history of Islam.…”
Section: çAtalhöyükmentioning
confidence: 99%
“…While it is important to protect and preserve the Islamic and Ottoman heritage and it is only natural that people will value the particular version of the past that reflects and legitimizes their worldview, the lack of the community's identification with the prehistoric site of Çatalhöyük is largely the outcome of statesupported school education, which prioritizes family, national, and religious identity. By contrast, prehistoric and other eras of antiquity, which are seen as largely unrelated to contemporary Turkish identity, are given little coverage (Apaydin 2016a). As a member of this community stated:…”
Section: çAtalhöyükmentioning
confidence: 99%
See 2 more Smart Citations